The Research of Educational Management for Entrepreneurship Based on Creativity Value Chain - Chen, Zhiguo (International Journal of Development Administration Research, 2025)
Cultivating the spirit of innovation and entrepreneurship is a concrete manifestation of the comprehensive national strength of the sustainable development of a country and the people, which is realized by the young talent is the first resource, smoothly into a revolutionary innovation of science and technology productivity. The socialist modernization construction of an innovative country with Chinese characteristics requires the cooperation of the whole society in efforts for higher education. With China’s comprehensive strength and core competitiveness of demand for innovative talents, management has aroused great attention from the domestic educational circles and the theory of innovative talents cultivation in universities. Higher education management process must strengthen the cultivation of contemporary college students’ awareness of innovation, entrepreneurship, and entrepreneurial ability in talent, so that in the fierce competition in the job market is not only capable of self-occupation, flexible employment, but also to actively do pioneering work independently, be innovative talents. Services in the construction of an innovation-oriented country need to be diversified, and multi-level innovative entrepreneurial talent, which requires high education in China, and the whole society should strive to promote the implementation of entrepreneurship education management innovation. This study use questionnaire to collect data from a total of 500 respondents, aiming to explore the factors which has influence on entrepreneurship education management. The results show that the entrepreneurship education management needs various supports from the stakeholders involved in the creativity value chain.